Элементный состав багульника болотного; Химия растительного сырья; № 4 - Белоусов М. В. Михаил Валерьевич; Цыбукова Т. Н.; Березовская Т. П.; Тихонова О. К.; Басова Е. В.; Зейле Л. А.; Юсубов М. С. Мехман Сулейман-оглы (Сулейманович) (2002, 2002)
Заглавие с экрана